Peningkatan pengetahuan pengelolaan obat yang tepat pada masyarakat Kelurahan Candirenggo RW 07 melalui sosialisasi DAGUSIBU obat - Maulida, Faradillah (Maliki Interdisciplinary Journal, 2024)
Certain sections of the public have a problem in managing medicine properly. One cause is that not everyone knows how to treat their illnesses using various types of medicine. Various medicine-related problems that occur in the community can be contributed to by a lack of knowledge about the correct use and management of medicine. To inform the community about proper medicine management, one of the ways is through the implementation of DAGUSIBU (DApatkan, GUnakan, SImpan, BUang). Based on the information collected, the community in Candirenggo Sub-district had never received information about DAGUSIBU, therefore it was needed to socialize DAGUSIBU in this community. The purpose of this activity is for the community to understand and share information with their families and neighbours about the accuracy of receiving, using, storing, and disposing of medicines. The method used was through socialization or lectures, interactive discussions, and handing out DAGUSIBU brochures. Participants were enthusiastic in listening the presentation and asking questions about medicine use and treatment. This can support the government's programs in increasing healthcare for the community. This socialization increased their knowledge on how to manage medicines properly, as well as sharing the knowledge gained with the surrounding environment to be applied.